Measuring the value of online communities and networks of practice for business - Yap, Robin; Robben, Joost (Proceedings of the International Conference on Networked Learning, 2012)
How are you measuring the value of your online communities and networks of practice? This research-in-progress paper identified the landscape of social networks, networked learning, and social network technologies. Based upon Wenger’s et al. (2011) framework on promoting and assessing value creation in communities and networks, a model has been identified to measure the success of the organization’s “knowledge collective” - the dialogue and learning in online communities and networks of practice in corporate environments. In our rapidly changing workplace landscape, augmenting formal performance improvement activities are informal learning and coaching incorporating social network technologies to increase involvement, strengthen relationships, and enhance individuals’ development. The methodology for the research study has been presented and used in conducting two concurrent studies in two countries (Netherlands and Canada). Preliminary results of the two studies will be presented at the conference and upon completion of the research, the results will be incorporated into this paper. The model presented in this study will provide an evidence-based instrument for organizations to measure the value of the dialogue in online communities to achieve business results.